The Miíkmaq, Poor Settlers, and the Nova Scotia Fur Trade, 1783-1853 - Gwyn, Julian (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2003)
AbstractNova Scotia's fur trade has hitherto been overlooked. It was of small importance so long as hostilities dominated Nova Scotia until 1758-60. Once peace settled on the colony, and when the Mi'kmaq of Nova Scotia held a virtual monopoly on trapping, the trade remained of little consequence. The principal source of the harvested furs was neither Cape Breton nor peninsular Nova Scotia, but the upper Saint John River Valley in Maliseet territory, and much of it was exported to London via Boston. With the influx of loyalist refugees in the 1780s, the fur trade in what remained of Nova Scotia began in earnest. This view, based on an extensive examination of British Customs House records, is contrary to what previous historians have stated. Led by Nova Scotia's harvest of mink and fox, which represented, after 1810, between 20% and 25% of the annual exports from British North America to London, the colony's fur trade remained vigorous until the 1860s. Much of this increased production, exported from Halifax, resulted from the efforts of poor settlers, who successfully challenged the Native monopoly, as the Nova Scotia Mi'kmaq, from the 1780s, were pushed to the very brink of extinction as a people.